Direct arylation polymerization toward efficient synthesis of benzo[1, 2‐c:4, 5‐c'] dithiophene‐4, 8‐dione based donor‐acceptor alternating copolymers for organic optoelectronic applications. Issue 22 (11th October 2018) - Bohra, Hassan; Chen, Hui; Peng, Yanfen; Efrem, Amsalu; He, Feng; Wang, Mingfeng
ABSTRACT: Wide‐bandgap π‐conjugated donor‐acceptor (D‐A) alternating copolymers consisting of benzo[1, 2‐c:4, 5‐c']dithiophene‐4, 8‐dione (BDTD) as the electron‐accepting building block have demonstrated outstanding performances in organic bulk heterojunction (BHJ) solar cell devices. But the synthesis of these polymers has been largely limited to conventional polymerization techniques, particularly Stille‐coupling based polycondensations, which often involve tedious preactivation of C‐H bonds using highly flammable reagents such as butyl lithium and highly toxic reagents such as trialkyl tin chlorides. Herein, we report a "greener" synthetic route of direct arylation polymerization to a series of wide bandgap D‐A copolymers with a common acceptor building block of BDTD. The structure–property relationship in these polymers is characterized. We also present the device performances of these polymers in both thin‐film field‐effect transistors and organic BHJ solar cells involving the BDTD‐based polymers as the electron donors and fullerene derivatives as the electron acceptors. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2554–2564 Abstract : Three donor‐acceptor polymers containing benzo[1, 2‐c:4, 5‐c']dithiophene‐4, 8‐dione (BDTD) are synthesized by direct arylation polymerization and their structure and optical properties are studied. Polymer containing quarterthiophene as the donor (P3) shows aggregation in solution state and BJH organic solar cells fabricated using P3 and PC71 BM show power conversion efficiencies up to 3.5%.